A molecular imprinted fluorescence sensor based on carbon quantum dots for selective detection of 4-nitrophenol in aqueous environments. (February 2023) - Wang, Kunpeng; Tan, Liju; Zhang, Yuewei; Zhang, Dongmei; Wang, Na; Wang, Jiangtao
Abstract: P-nitrophenol (4-NP) is the most persistent and highly toxic species among nitrophenol. In this work, a novel fluorescent probe for the detection of 4-NP in aqueous environment was constructed by combining the carbon dots (CQDs) with excellent optical properties and the molecularly imprinted polymer (MIP) with favorable selectivity. The CQDs were synthesized by hydrothermal method using citric acid hydrate as carbon source and o -phenylenediamine as surface modifier, then the molecularly imprinted polymers coating on the CQDs (MIP@CQDs) were obtained by sol-gel imprinting process. The fluorescence quenching of MIP@CQDs is the results of internal filtration effect and dynamic quenching when they encounter with 4-NP. The probe is suitable for the quantitative detection of trace 4-NP in actual aqueous samples, such as tap water, wastewater and seawater, with satisfying recoveries from 95.1 % to 107.8 %, wide detection linear ranges between 0 and 144 μmol/L, low detection limit of 0.41 μmol/L and high selectivity. The detection results are consistent with those of the HPLC method. This work provides a simple, rapid and effective fluorescent detection method for trace 4-NP in aqueous environment. Highlights: High performance sensor was fabricated using carbon quantum dots combined with molecular imprinting for rapid determination of 4-NP in aqueous environment. The sensor of MIP@CQDs have good selectivity for 4-NP and enable the determination in complex environments. The determination results of the sensor were in good agreement with the HPLC method. The mechanisms of 4-NP bursting by MIP@CQDs are internal filtration effect and dynamic quenching.